Managing political risk in international project operations: The case study of a developed multinational enterprise (DMNE) in emerging markets (EMs). - Hossan, MD Zakir (My University, 2020)
This research investigates the perception and management of political risks by the developed country multi-national enterprise (DMNE) when undertaking infrastructure development projects in emerging markets (EMs). The study adopted 11 political risk elements and 16 political risk management strategies/mechanisms. The theoretical framework of the study is derived from the relevant literature review of social exchange/institution theory, transaction cost theory, project management literature, and finance literature. This framework is empirically tested based on an exploratory mono-qualitative research methodology. A single case study and purposive sampling technique were utilized to obtain interview data from four of the project managers of Wärtsilä Corporation, Finland over the summer of 2020. The study finds that managing political risks in (international project operations) IPOs has been found extremely important for Wärtsilä’s success in the selected IPO case countries. The study finds that only 5 of the 11 identified political risk elements have received empirical evidence of causing tensions in Wärtsilä’s operation in the investigated countries. Whereas, out of the 16 identified political risk management strategies only 10 strategies were reaffirmed by the empirical findings. The empirical findings suggest that most of the respondent (100%) have utilized and perceived developing personal relationship approach, adopting a localization strategy, avoiding business misconduct, etc. as effective measures against political risks management. Besides these findings, an interesting empirical finding is utilizing The Embassy of Finland’s help in China to get access to Chinese higher authorities. This strategy has found to be particularly important as China practices a hierarchical power distance method. Furthermore, as a novelty of this research endeavour, the empirical findings suggest that a certain political risk management strategy assisted the case company to control or reduce specific political risk elements in its respective IPOs. For instance, specifying the medium of business transactions in € Euro (Euroization) assisted the company to avoid currency inconvertibility political risk in all of the investigated IPOs.
Keywords: risk management; risks; project management; projects; business; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business